Sentiment, order imbalance, and co-movement: An examination of shocks to retail and institutional trading activity - Chelley-Steeley, Patrìcia Lorraine; Lambertides, Neophytos; Savva, Christos S. (My University, 2019)
Using order flow imbalance as a measure of sentiment we show that positive and negative shocks to sentiment lead to lower co-movement between portfolio and market returns in the post-shock period. Furthermore, an asymmetry is present as positive shocks to sentiment have less impact on co-movement changes than negative shocks. Moreover, shocks to retail sentiment and the sentiment of two types of institutional investors lead to a reduction in co-movement. Positive shocks to institutional order flow imbalance lead to smaller reductions in co-movement than associated with retail shocks. These effects exist even after controlling for firm-specific and market-wide news.
Keywords: Co-movement; Order flow shock and sentiment; Smooth transition model